1989
DOI: 10.1021/ja00191a063
|View full text |Cite
|
Sign up to set email alerts
|

Borohydride boron-hydrogen activation and dimerization by a doubly bonded, early-transition-metal organodimetallic complex. Ditantalladiborane syntheses as models for dehydrodimerization of methane to ethane

Abstract: The 2-D INEPT-INADEQUATE spectrum for 7 (Figure 2) is also irrefutable evidence for structural identification.7 Note that 8 (Figure 3b) would show a connected to b and b connected to c. The spectrum clearly shows a directly bonded to both b and c, with two-bond coupling between b and c and three-bond coupling between c and d.10•11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 2 publications
5
60
0
1
Order By: Relevance
“…Despite the availability of well-developed routes to metallaboranes of Group 6-9 metals, to our knowledge examples of characterized Group 5 metallaboranes are very rare. [21] Tantalaboranes [(Cp*Ta) 2 A C H T U N G T R E N N U N G (B 2 H 6 ) 2 ] [22] and [(Cp*Ta)Cl 2 B 4 H 8 ] [23] were synthe- (4) in modest yield. Compounds 1-3 are air-and moisture-sensitive but 4 is reasonably stable in air.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of well-developed routes to metallaboranes of Group 6-9 metals, to our knowledge examples of characterized Group 5 metallaboranes are very rare. [21] Tantalaboranes [(Cp*Ta) 2 A C H T U N G T R E N N U N G (B 2 H 6 ) 2 ] [22] and [(Cp*Ta)Cl 2 B 4 H 8 ] [23] were synthe- (4) in modest yield. Compounds 1-3 are air-and moisture-sensitive but 4 is reasonably stable in air.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless the BeB distance (1.907 A) which is longer than the usual bridged B 2 (m-H)M (M ¼ Ru) one (1.733e1.840) [13,16,20,53,54] in the complexed state, does not support this view. In the bimetallic species (C 5 Me) 2 Ta 2 (mBr) 2 (B 2 H 6 ) [55], the BeB bond exhibits a close distance to ours (1.88 A). It has been concluded that this parameter is not consistent with a strong BeB bond.…”
Section: Structural and Energetic Analysis Of [Hfe(co) 4 (B 2 H 5 )]mentioning
confidence: 78%
“…Although the reaction of metal chlorides with borohydride is a known method for the production of hydrides (and reduction of the metal center), what has not been appreciated is the fact that conversion of a polychloride to a polyborohydride permits H elimination with the formation of BB and MB bonds to be competitive with loss of borane to form a polyhydride. It was the work of Ting and Messerle (23), that demonstrated this unambiguously for the "rst time. In contrast, something unanticipated before our work is the fact that BH THF readily reacts with the same substrates to form metallaboranes with the chlorine being eliminated as BH Cl in all cases except one.…”
Section: A General Synthesis Of Metallaboranesmentioning
confidence: 87%